Klasifikasi Kemampuan Ekonomi Calon Siswa Baru dengan Metode K-Nearest Neighbor pada SMA Negeri 1 Musi Rawas - Soleha, Romi Aprillia; Wijaya, Harma Oktafia Lingga; Daulay, Nelly Khairani (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
The need for an analysis of the classification at SMA Negeri 1 Musi Rawas was the reason for conducting research on the clasification of the economic abilities of new student, determining classification in large numbers was impossible to do manually because it required quite a long time. For that we need a method that can solve classification problems automatically with a computer. in classifying an application in the form of orange is used and in analyzing using the K-Nearest Neighbor method because it has the working principle of fiding the shortest distance between the data to be evaluated with the nearest K in the training data. This study aims to apply the orange application using the K-Nearest Neighbor method and find out what the level of accuracy is with the K-Nearest Neighbor method. From this study the training data is 150 and testing 1 with a K value of 50 gets an accuracy value of 92%.